Serum Leptin Level and Thyroid Hormone in Type 2 Diabetes Patients (Medico Legal Update, 2021)
Background: Diabetes is a complex, chronic illness requiring continuous medical care with multi-factorialrisk-reduction strategies beyond glycemic control. Ongoing diabetes self-management education andsupport are critical to preventing acute complications and reducing the risk of long term complications(1).Diabetes mellitus occurs when there are raised levels of glucose in aperson’s blood because their bodycannot produceany or enough of the hormone insulin, or cannot effectively use the insulin it produces.The causes of type 2 diabetes are not completely understood but there is a strong link with overweightand obesity, and increasing age, as well as with ethnicity and family history.Aim: This study intended toassess and study correlation between serum levels of leptin and thyroid hormones in diabetic and obesepatients.Subject and Method:a case control study was conducted at the center of diabetes managementand research between 1st of December 2019 to the 15th of May 2020. A fasting blood sample was takenfrom all participants for measurement of biochemical parameters. The information regarding the problemand demographic characteristics was obtained directly from the participants by interviewing them, using aprepared questionnaire. The weight and the height were using a medical scale machine. The body mass indexwas calculated according to its equation.Results: Results of the present study show that leptin hormone wassignificantly high in serum of type 2 diabetic patients group compared with overweight and obese group (P< 0.000). A significant positive correlation with serum leptin and body mass index. Results also show thatTSH hormone (P < 0.01), and FBS were significantly high(P < 0.000), while T3 and T4 decrease significant(P < 0.05) in type 2 diabetic patients groupand compared with control groups.